The social network context of HIV stigma: Population-based, sociocentric network study in rural Uganda - Takadaa, Sae; Nyakato, Viola; Nishi, Akihiro; O'Malley, A. James; Kakuhikire, Bernard; Perkins, Jessica M.; Bangsbergh, David R.; Christakisi, Nicholas A.; Tsai, Alexander C. (Social Science & Medicine, 2019)
Rationale: HIV-related stigma profoundly affects the physical and social wellbeing of people living with HIV, as well as the community’s engagement with testing, treatment, and prevention. Based on theories of stigma elaborating how it arises from the relationships between the stigmatized and the stigmatizer as well as within the general community, we hypothesized that social networks can shape HIV-related stigma. Objective: To estimate social network correlates of HIV-related stigma. Methods: During 2011-2012, we collected complete social network data from a community of 1669 adults (“egos”) in Mbarara, Uganda using six culturally-adapted name generators to elicit different types of social ties (“alters”). We measured HIV-related stigma using the 9-item AIDS-Related Stigma Scale. HIV serostatus was based on self-report. We fitted linear regression models that account for network autocorrelation to estimate the association between egos’ HIV-related stigma, alters’ HIV-related stigma and alters’ self-reported HIV serostatus, while adjusting for egos’ HIV serostatus, network centrality, village size, perceived HIV prevalence, and sociodemographic characteristics. Results: The average AIDS-Related Stigma Score was 0.79 (Standard Deviation=0.50). In the population 116 (7%) egos reported being HIV-positive, and 757 (46%) reported an HIV-positive alter. In the multivariable model, we found that egos’ own HIV-related stigma was positively correlated with their alters’ average stigma score (b=0.53; 95% confidence interval [CI] 0.42-0.63) and negatively correlated with having one or more HIV-positive alters (b=-0.05; 95% CI -0.10 to -0.003). Conclusion: Stigma-reduction interventions should be targeted not only at the level of the individual but also at the level of the network. Directed and meaningful contact with people living with HIV may also reduce HIV-related stigma
Keywords: Population-based; Network; HIV stigma; Uganda